Effect of welding parameters on microstructure and mechanical properties of friction stir welded joints of a super high strength Al–Zn–Mg–Cu aluminum alloy. (15th February 2015) - Zhang, Fei; Su, Xuekuan; Chen, Ziyong; Nie, Zuoren
Abstract : Graphical abstract: The histogram shows the average tensile properties in transverse orientation of the BM and different welding parameters. Highlights: A new kind of super high strength Al–Zn–Mg–Cu aluminum was friction stir welded. The welding characteristics of the experimental alloys were discussed. Mechanical heterogeneity of welded joints was analyzed based on observations of microstructure. Abstract: Samples made of a super high strength aluminum alloy with high Zn content were friction stir welded with rotation rates of 350–950 rpm and welding speeds of 50–150 mm/min. The effect of welding parameters on the microstructure and mechanical properties was investigated. It was observed that the grain size of the nugget zones decreased with the increasing welding speed or the decreasing tool rotation rate. Most of the strengthening precipitates in the nugget zone were dissolved back and the intragranular and grain boundary precipitates in the heat affected zone coarsened significantly. The greatest ultimate tensile strength of 484 MPa and largest elongation of 9.4 were obtained at 350 rpm−100 mm/min and 350 rpm−50 mm/min, respectively. The ultimate tensile strength and elongation deteriorated drastically when rotation rate increased from 350 to 950 rpm at a constant welding speed of 100 mm/min.